Perioperative Urinary Catheter Use and Association to (Gram-Negative) Surgical Site Infection after Spine Surgery - Alexandre Ansorge; Michael Betz; Oliver Wetzel; Marco Dimitri Burkhard; Igor Dichovski; Mazda Farshad; Ilker Uçkay (MDPI AG, 2023)
This study evaluates potential associations between the perioperative urinary catheter (UC) carriage and (Gram-negative) surgical site infections (SSIs) after spine surgery. It is a retrospective, single-center, case-control study stratifying group comparisons, case-mix adjustments using multivariate logistic regression analyses. Around half of the patients (2734/5485 surgeries) carried a UC for 1 day (median duration) (interquartile range, 1-1 days). Patients with perioperative UC carriage were compared to those without regarding SSI, in general, and Gram-negative, exclusively. The SSI rate was 1.2% (67/5485), yielding 67 revision surgeries. Gram-negative pathogens caused 16 SSIs. Seven Gram-negative episodes revealed the same pathogen concomitantly in the urine and the spine. In the multivariate analysis, the UC carriage duration was associated with SSI (OR 1.1, 95% confidence interval 1.1-1.1), albeit less than classical risk factors like diabetes (OR 2.2, 95%CI 1.1-4.2), smoking (OR 2.4, 95%CI 1.4-4.3), or higher ASA-Scores (OR 2.3, 95%CI 1.4-3.6). In the second multivariate analysis targeting Gram-negative SSIs, the female sex (OR 3.8, 95%CI 1.4-10.6) and a UC carriage > 1 day (OR 5.5, 95%CI 1.5-20.3) were associated with Gram-negative SSIs. Gram-negative SSIs after spine surgery seem associated with perioperative UC carriage, especially in women. Other SSI risk factors are diabetes, smoking, and higher ASA scores.